18 Baseline coronary flow varies with normal cardiac catheter laboratory stimuli. (24th April 2016) - Modi, Bhavik N; Ellis, Howard; Arri, Satpal; Lumley, Matthew; Briceno, Natalia; Williams, Rupert; Clapp, Brian; Redwood, Simon; Marber, Michael; Perera, Divaka
Abstract : Introduction: Fractional Flow Reserve (FFR) is a pressure-derived estimate of coronary flow impairment during maximal and constant hyperaemia provided by an adenosine infusion, when flow and pressure approximate linearly. The need for adenosine-induced hyperaemia has led to development of a stenosis severity index measured at rest, Instantaneous Wave Free Ratio (iFR). Its use and proposed applicability to serial/diffuse disease has relied on assumptions that coronary flow at rest is maintained at constant levels. This study aimed to assess variability of resting coronary flow with normal Catheter laboratory stimuli. Methods: Forty-Seven elective patients were recruited with a variety of coronary artery disease severity (mean FFR: 0.883; SD: 0.938). Simultaneous intracoronary pressure (Pd) and Doppler Average Peak Flow Velocity, APV(U), recordings were made. These were made both at rest and just prior to supine bicycle exercise or intravenous adenosine infusion. Results: Average peak flow velocity varied significantly between measurements at rest and just prior to commencement of adenosine or supine bicycle exercise (18.1765cm/s vs. 19.4689cm/s, p 0.002). This was without significant change in haemodynamics (Table 1 ). Conclusion: Resting coronary flow appears to vary significantly with normal Catheter Laboratory stimuli, such as simple warnings, irrespective of haemodynamic status.